2011
DOI: 10.1038/leu.2011.289
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP7 participates in the reciprocal interaction between acute lymphoblastic leukemia and BM stromal cells and in leukemia resistance to asparaginase

Abstract: The interaction of acute lymphoblastic leukemia (ALL) blasts with bone marrow (BM) stromal cells (BMSCs) has a positive impact on ALL resistance to chemotherapy. We investigated the modulation of a series of putative asparaginase-resistance/ sensitivity genes in B-precursor ALL cells upon coculture with BMSCs. Coculture with stromal cells resulted in increased insulinlike growth factor (IGF)-binding protein 7 (IGFBP7) expression by ALL cells. Assays with IGFBP7 knockdown ALL and stromal cell lines, or with add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…Our results complement the recent finding that bone marrow-derived mesenchymal cells (MSCs) protect leukemia from ASNase treatment through ASN secretion (1921). Laranjeira et al showed that leukemia-cell secretion of IGFBP-7 increased ASN synthesis by stromal cells (21).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results complement the recent finding that bone marrow-derived mesenchymal cells (MSCs) protect leukemia from ASNase treatment through ASN secretion (1921). Laranjeira et al showed that leukemia-cell secretion of IGFBP-7 increased ASN synthesis by stromal cells (21).…”
Section: Discussionsupporting
confidence: 89%
“…As adipose tissue is a major contributor to the whole body GLN pool (16), obesity may impair GLN depletion. Moreover, it has been proposed that non-malignant cells might support leukemia cells during ASNase treatment through local secretion of amino acids (17), an idea that has been further explored more recently (1821). …”
Section: Introductionmentioning
confidence: 99%
“…The BM microenvironment can also play a role in leukemia drug resistance, mediated by a diverse set of mechanisms, both by direct cell adhesion 11,13,27 and/or soluble factor release. 12,20,28,29 In this study, the protective effects of MSC against PTL toxicity were related to decreases in ROS stress and preserved rGSH levels, suggesting that MSC increased the anti-oxidative stress capacity of T-ALL cells and thereby conferred resistance to PTL. To eliminate variability, MSC were generated from a single normal BM donor, allowing direct comparison of the effects on the patients’ samples.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, IGFBP7 plays a positive, contributing role in the interaction between leukemia cells and the microenvironment, which may promote the leukemic cell adhesion, invasion and migration (31). another assay with IGFBP7 knockdown and acute lymphoblastic leukemia (aLL), showed that IGFBP7 acts as a positive regulator of aLL and stromal cell growth, and significantly enhances in vitro resistance of aLL to sparaginase (32). Hypomethylation of IGFBP7 is likely to characterize an immature and a more malignant subtype of the disease (33).…”
Section: Discussionmentioning
confidence: 99%